Postural and muscle responses to galvanic vestibular stimulation reveal a vestibular deficit in adolescents with idiopathic scoliosis. (7th August 2019) - Hatzilazaridis, Ioannis; Hatzitaki, Vassilia; Antoniadou, Nikoleta; Samoladas, Efthimios
Abstract: One of the most appealing hypotheses around the aetiopathogenesis of adolescent idiopathic scoliosis attributes the development of the spine deformity to an imbalance in the descending vestibulospinal drive to the muscles resulting in a differential mechanical pull on the spine during the early life stages. In this study, we explored this hypothesis by examining postural and muscle responses to binaural bipolar galvanic vestibular stimulation (GVS) of randomly alternating polarity. Adolescents diagnosed with idiopathic scoliosis ( n = 12) and healthy age‐matched controls ( n = 12) stood quietly with feet together (stance duration 66–102 s), eyes closed and facing forward, while 10 short (2s), transmastoidal, bipolar square wave GVS pulses (0.3–2.0 mA) of randomly alternating polarity were delivered at varying time intervals. Responses depicted in the electromyographic (EMG) activity of bilateral axial and appendicular muscles, vertical reaction forces and segment kinematics were recorded and analysed. Scoliotic patients demonstrated smaller ankle muscle responses and a delayed postural shift to the right relative to controls during anode right/cathode left GVS. When GVS polarity was reversed, patients had a greater soleus short‐latency response on the left anodal side, while the rest of the muscle and postural responses were similar between groups. Vestibular stimulation also evoked greater head and upper trunk sway in scoliotic compared with healthy adolescents irrespective of stimulus polarity. Results provide new preliminary evidence for a vestibular imbalance in adolescents with idiopathic scoliosis that is compensated by somatosensory, load‐related afferent feedback from the lower limbs during the latter part of the response. Abstract : We analysed the asymmetry of postural and muscle responses to galvanic vestibular stimulation of alternating polarity in order to test the hypothesis attributing the origin of adolescents' idiopathic scoliosis to a vestibular imbalance. Results reveal for the first time in humans, an early asymmetry in the ankle muscle responses favouring the hypothesis of a vestibular imbalance that is compensated by somatosensory, load‐related afferent feedback, later on during the response.